Inorganic sulfate is critical for Mycobacterium tuberculosis lung tissue colonization and redox balance - Wendy Le Mouëllic; Florence Levillain; Ting-Di Wu; Maxime Caouaille; Philippe Bousso; Yannick Poquet; Olivier Neyrolles (Proceedings of the National Academy of Sciences, 2025)
Tuberculosis remains the deadliest infectious disease caused by a single pathogen, highlighting the urgent need for novel therapies. A deeper understanding of Mycobacterium tuberculosis metabolism could uncover specific vulnerabilities and inform the development of new treatments. Sulfur, essential for bacterial growth and survival, fuels key pathways including redox buffering and coenzyme production. Although previous studies suggest that M. tuberculosis utilizes various substrates to meet its sulfur requirements, the primary sources of sulfur exploited during in vivo infection remain unclear. Here, we reveal that M. tuberculosis acquires inorganic sulfate through the SubI-CysTWA transporter during macrophage infection. Using nanoSIMS (high spatial resolution Secondary Ion Mass Spectrometry) analysis, we observed significant sulfate-derived 33 S enrichment in intracellular bacteria, correlating with metabolic activity. Deletion of subI abolished sulfate uptake, impairing bacterial growth in vitro and reducing M. tuberculosis survival in murine macrophages and lungs of infected mice. Finally, our data demonstrate that sulfate acquisition is essential for maintaining mycobacterial redox balance and resisting nitrosative stress in vitro and in vivo. Thus, unlike many intracellular pathogens, M. tuberculosis depends on an energetically costly inorganic sulfate assimilation pathway to survive in the nutrient-limited host environment. These findings challenge prior assumptions that organic reduced sulfur sources, such as methionine, fuel M. tuberculosis sulfur metabolism during infection. Since animal cells lack a sulfate assimilation pathway, uncovering the critical role of SubI-CysTWA-mediated sulfate import in M. tuberculosis pathogenesis highlights this pathway as a promising pathogen-specific therapeutic target. Targeting this system could either directly impair M. tuberculosis survival during infection or sensitize bacilli to antibiotic-induced oxidative stress by disrupting redox homeostasis.